SEMINAR PENDIDIKAN: PENTINGNYA KOMUNIKASI INTERPERSONAL GURU DALAM MEMBENTUK PRESTASI BELAJAR SISWA - Isna Siskawati (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Communication between teachers and students is a determining factor for students' success in understanding the material presented in class. Devotion is carried out to provide knowledge to teachers about teacher interpersonal communication techniques in providing material with the aim that the learning process takes place interactively and the material is conveyed appropriately. The service method is carried out using a one-day seminar approach which is carried out face to face to 36 teachers at Rahmania Islamic School Tangerang Selatan with the observation stage, making permits, preparing materials and conducting seminars. The results of the dedication show: the seminar was attended by all teachers running successfully and smoothly. The seminar was carried out with an opening by giving an appeal by the school owner, giving material pride to be a teacher, discussion part 1, giving interpersonal communication material to teachers, discussion part 2, interpersonal effective communication and positif language practices and ending with thanksgiving and prayer